2006
DOI: 10.1097/01.ta.0000215565.29846.ab
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Hyperglycemia and Insulin Therapy on Outcome in a Hyperglycemic Septic Model of Critical Illness

Abstract: Hyperglycemia is associated with greater morbidity and mortality in sepsis. Insulin therapy significantly improved survival suggesting that management of hyperglycemia with insulin may improve outcome in septic patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
12
0
2

Year Published

2007
2007
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 47 publications
2
12
0
2
Order By: Relevance
“…Stressinduced hyperglycaemia frequently occurs in infection and is associated with an adverse outcome [14,48]. Elevated TNFα levels, increased MCP-1 production as well as low adiponectin may act in concert to induce and to maintain hyperglycaemia in critical illness.…”
Section: Discussionmentioning
confidence: 99%
“…Stressinduced hyperglycaemia frequently occurs in infection and is associated with an adverse outcome [14,48]. Elevated TNFα levels, increased MCP-1 production as well as low adiponectin may act in concert to induce and to maintain hyperglycaemia in critical illness.…”
Section: Discussionmentioning
confidence: 99%
“…Heuer et al (11) reported that hyperglycemic and septic rodents had higher levels of cytokines/chemokines, serum organ damage markers and reduced survival. In a rabbit model of critical illness, elevated blood glucose induced by alloxan administration evoked cellular glucose overload, inducing mitochondrial dysfunction (12).…”
Section: Introductionmentioning
confidence: 99%
“…During a bout of sepsis, whole body metabolism is shifted into a catabolic state, the most marked features of which include increased resting energy expenditure, hyperglycemia, and rapid muscle loss (4). Attenuation of each of these features is associated with a reduction in associated mortality (5)(6)(7). A prime mediator of the response to sepsis is a rapid increase in catecholamine levels and sympathetic activation (8).…”
mentioning
confidence: 98%